The body mass index and reflex reaction connection: insights into upper limb reflexes in young adults - Thankachan, Tinu; K. B., Riyas Basheer; Rai, Subhashchandra; Kolar, Reshma (International Journal of Research in Medical Sciences, 2025)
Background: Reflexes are automatic responses to stimuli, enabling quick reactions through reflex arcs. Body Mass Index (BMI) influences various physical and cognitive functions, and deviations from optimal BMI may impact reflex reactions. This study aimed to investigate the correlation between BMI and upper limb reflex reaction in young adults aged 18-25 years, emphasizing the importance of maintaining a healthy BMI. Methods: This observational, cross-sectional study involved 51 participants (14 females, 37 males) from an institution in Mangalore. Data such as height, weight, and reflex reaction time were collected. BMI was calculated using the WHO classification (2004), and upper limb reflex time was assessed using the Ruler Drop Test. Each participant underwent three trials, and the average distance was analyzed. Statistical analysis was performed using SPSS 21.0, applying Pearson correlation to evaluate relationships between BMI and reflex reaction (p<0.05). Results: The study revealed a moderate negative correlation between BMI and upper limb reflex reaction time (r = -0.437). Participants with higher or lower BMI beyond the optimal range showed slower reflex responses. Males exhibited slightly quicker reflexes (28.25±6.18 cm) compared to females (30.25±7.20 cm). Conclusions: Deviations in BMI negatively impact upper limb reflex response in young adults, highlighting the need for maintaining an optimal BMI for efficient neuromuscular functioning.